A Sensitive Carbon Paste Electrode for Selective Detection of Lead Based on the Synergistic Effect of Bismuth and Chelating Agent. (9th November 2020) - Yang, Qingui; Yang, Chun; Yi, Jian; Fan, Gaochao; Yang, Haipeng; Ge, Zaochuan
Abstract : A new type of carbon paste electrode (CPE) has been prepared by mixing bismuth oxide, diphenyl thiocarbazone and graphite powder (Bi-Di-CPE). Trace amount of Pb 2+ has been detected via the differential pulse stripping voltammetry (DPV) method with Bi-Di-CPE, which exhibits an extremely high sensitivity about lead. The peak current of Bi-Di-CPE has a linear relationship with the concentration of lead in the range of 5–80 μ g l −1, and the limit of detection is as low as 0.15 μ g l −1, which meets the detection requirements of heavy metals in tap water (Pb ≤ 10 μ g l −1 ) or in river water (Pb ≤ 50 μ g l −1 ). The diphenyl thiocarbazone acts as a chelating agent which can selectively enriching lead. The bismuth oxide can provide bismuth film and further enriches the lead as a bismuth electrode in the electrodeposition process. The synergistic effect of the chelating agent and bismuth film of the Bi-Di-CPE brings high sensitivity and selectivity to detect heavy metals. Different kinds of modified CPE sensors towards different heavy metals with low cost and high performance may be achieved conveniently by using bismuth particles and corresponding chelating agents.